Três ensaios sobre discriminação no mercado de trabalho - Cavalcante, Alexsandre Lira (2015)
This thesis is formed by the junction of three studies in Microeconometrics area related to the Brazilian labor market, seeking to raise questions that try to explain the pay gap between different groups present in this market. In each chapter was used three different methods of estimation with the use of different databases. In the first chapter, Analysis of Wage Differentials in the Brazilian labor market from the Sexual Orientation, sought to measure the wage differential from sexual orientation in the Brazilian labor market, using the new methodology of identification of family arrangements presented in Census 2010 (IBGE). After estimating the wage equations with correction of sample selection bias proposed by Heckman (1979) the results pointed in the direction of non-discrimination against minorities of gays and lesbians in the national labor market. The second chapter, Counterfactual decomposition of Oaxaca - Blinder Wage Differentials by Gender and Race in the Brazilian Private Job Market with Bias Correction Sample Selection: An Analysis for Economic Sectors and Types of Occupations, made use of the National Household Survey database IBGE (2013), when it sought to analyze the root causes of wage inequality by gender and race in the Brazilian private labor market detailing by sectors of economic activity and types of occupation. To achieve this goal we used the wage decomposition methodology on average proposed by Oaxaca - Blinder (1973), after the estimation of wage equations when the corrections were also made of the sample selectivity. The main results pointed to the importance of human capital variables to explain much of the wage gap between white men and other groups investigated via differences appropriations, in particular the variable schooling that helps reduce the wage differential between white men and white and black women. Noteworthy is the participation in some types of occupations when white and black women earn on average more than white men. Finally, the high participation and representativeness of the intercept term, the wage differential explanation by gender and race, both in the overall labor market, as in most economic sectors and types of occupations investigated explains most of this phenomenon when the white man earns more , simply because he is man and white. The third and final chapter, Structural Changes in Education Returns and Differential Wage Race for Gender in Brazil for Different Groups of Age: An Approach of quantile regression with bias correction of Sample Selection, made use of the National Household Survey 2003 and 2013 and quantile regression techniques with selection bias correction proposed by Buchinsky (1998b) to analyze changes in the returns to education and racial differentials by gender wage and age groups in the Brazilian labor market between 9 the two years. Different values for the returns of schooling and racial differences were mainly observed in the highest quantile of the distribution of wages for almost all age groups. The wage returns of women were above the wage returns of men for all estimated quantile in all age groups in the two years analyzed. Finally, it is worth mentioning the reduction in wage returns to both sexes and the improvement in the standard of discrimination in the national labor market between the years 2003 and 2013.